2011
DOI: 10.1016/j.bbrc.2011.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong caloric restriction prevents age-induced oxidative stress in the sympathoadrenal system of Fischer 344 x Brown Norway rats

Abstract: Aging is associated with oxidative damage and an imbalance in redox signaling in a variety of tissues, yet little is known about the extent of age-induced oxidative stress in the sympathoadrenal system. Lifelong caloric restriction has been shown to lower levels of oxidative stress and slow the aging process. Therefore, the aims of this study were two-fold: 1) to investigate the effect of aging on oxidative stress in the adrenal medulla and hypothalamus and 2) determine if lifelong 40% caloric restriction (CR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Normal aging is associated with increases in circulating catecholamines (88), an effect that is associated with the induction of catecholamine biosynthetic enzymes in the adrenal medulla (99). CR has been shown to attenuate the expression of catecholamine biosynthetic enzymes (57) and reduce oxidative damage to the adrenal medulla (205). However, it is not clear whether long-term CR reduces circulating catecholamine levels (123).…”
Section: Effects Of Calorie Restriction On Cardiac Functionmentioning
confidence: 98%
“…Normal aging is associated with increases in circulating catecholamines (88), an effect that is associated with the induction of catecholamine biosynthetic enzymes in the adrenal medulla (99). CR has been shown to attenuate the expression of catecholamine biosynthetic enzymes (57) and reduce oxidative damage to the adrenal medulla (205). However, it is not clear whether long-term CR reduces circulating catecholamine levels (123).…”
Section: Effects Of Calorie Restriction On Cardiac Functionmentioning
confidence: 98%
“…7). Moreover, levels of enzymes involved in the metabolism of catecholamines have been shown to be increased with aging in the medulla [10,11,12], thus potentially worsening the situation. Interestingly, adjacent tissues can be affected as well, as exemplified by the zona reticularis of the AC in our study (fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, less is known about aging-induced structural changes in the AM, the catecholaminergic part of the gland. However, at the molecular level, it has been shown that levels of catecholaminergic enzymes are increased upon aging in the medulla of rodents [10,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…Increased level of MDA refl ected tissue damage (28), SOD and GSH are key anti-oxidant defense system enzymes to detoxify reactive molecules or repair the resulting damage in the cell (29).…”
Section: Discussionmentioning
confidence: 99%